2015
DOI: 10.1007/s10856-015-5446-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro response of human peripheral blood mononuclear cells to AISI 316L austenitic stainless steel subjected to nitriding and collagen coating treatments

Abstract: Surface modification treatments can be used to improve the biocompatibility of austenitic stainless steels. In the present research two different modifications of AISI 316L stainless steel were considered, low temperature nitriding and collagen-I coating, applied as single treatment or in conjunction. Low temperature nitriding produced modified surface layers consisting mainly of S phase, which enhanced corrosion resistance in PBS solution. Biocompatibility was assessed using human peripheral blood mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…When plasma nitrided (400 • C, 500 Pa, 5 h) and collagen coated AISI 316L samples were put in contact with HUVEC, significant higher cell proliferation was observed after 5 days for this sample type, in comparison with that registered for samples untreated and collagen coated or subjected only to plasma nitriding treatment, and a smaller release of metalloproteinase (MMP)-2, related to extracellular matrix degradation, was detected [223]. Biocompatibility of AISI 316L untreated and plasma nitrided (400 • C, 500 Pa, 5 h) with or without collagen coating was also tested incubating the samples with human PBMC [230]. The results showed that proliferation, viability and MMP-9 secretion were not negatively affected by the contact with the sample types, but a remarkable increase of the secretion of some pro-inflammatory cytokines was registered, in comparison with control cells.…”
Section: Biocompatibilitymentioning
confidence: 86%
See 2 more Smart Citations
“…When plasma nitrided (400 • C, 500 Pa, 5 h) and collagen coated AISI 316L samples were put in contact with HUVEC, significant higher cell proliferation was observed after 5 days for this sample type, in comparison with that registered for samples untreated and collagen coated or subjected only to plasma nitriding treatment, and a smaller release of metalloproteinase (MMP)-2, related to extracellular matrix degradation, was detected [223]. Biocompatibility of AISI 316L untreated and plasma nitrided (400 • C, 500 Pa, 5 h) with or without collagen coating was also tested incubating the samples with human PBMC [230]. The results showed that proliferation, viability and MMP-9 secretion were not negatively affected by the contact with the sample types, but a remarkable increase of the secretion of some pro-inflammatory cytokines was registered, in comparison with control cells.…”
Section: Biocompatibilitymentioning
confidence: 86%
“…The authors observed the same good level of cytocompatibility for untreated and treated samples when proliferation, apoptosis and cytokine released by HUVEC were considered, while cytokine released by PBMC and the increase in adhesion molecules levels suggested that consequences were occurring on a metabolic point of view. Low temperature nitriding has been reported to be a suitable treatment to act as a substrate for collagen coating [223,224,230]. When plasma nitrided (400 • C, 500 Pa, 5 h) and collagen coated AISI 316L samples were put in contact with HUVEC, significant higher cell proliferation was observed after 5 days for this sample type, in comparison with that registered for samples untreated and collagen coated or subjected only to plasma nitriding treatment, and a smaller release of metalloproteinase (MMP)-2, related to extracellular matrix degradation, was detected [223].…”
Section: Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lentulo spirals, due to their rotation motion, are prone to fracture with in the root canal system, 49 especially where there is reduced corrosion resistance due to repeated sterilization cycles. 50 Such an adverse outcome may further complicate endodontic treatment. 51 …”
Section: Discussionmentioning
confidence: 99%
“…The non-specific inflammatory response to implanted devices varies depending on their surface physicochemical properties, including surface chemistry, morphology and mechanics [12,13,14,15,16]. These properties affect the type, the quantity and the conformation of the adsorbed proteins, which determines the following interaction with adhesion receptors present on inflammatory cell populations, instigates a cascade of responses that are integral in determining the cellular driven inflammatory response, and constitutes the major cellular recognition system for implant materials [17,18].…”
Section: Introductionmentioning
confidence: 99%